Peningkatan aktivitas dan hasil belajar IPS peserta didik dengan menggunakan media pembelajaran “Sipete” - Martina Lona Jusita (Universitas Negeri Malang, 2018)
Understanding the Subthemes of Nature of Indonesia, especially on sub-theme Flora and Fauna will be more easily understood by learners based on the learning experience gained from the transfer of knowledge submitted by teachers. For that, teachers need to use a medium as an intermediary in learning. The appropriate learning medium is to use